Niwaella tigrina, a new species of spined loach from the Poyang Lake system of Jiangxi Province, East China - Zhang, Hai-Xin; Zhang, Yan-Ping; Chen, Wen-Jing; Zhang, E. (Zootaxa, 2025)
A new species of the spiny loach genus Niwaella is described herein from the Xiu-Shui river, an affluent of Lake Poyang in Jiangxi Province, China. This species is distinguished from all other congeneric species in China due to having a unique body coloration, comprising 20-25 transverse black bars on the dorsum and upper part of the flank. Other characteristics, though not exclusive to this species, include an indistinct blackish mid-dorsal stripe from the nape to the caudal-fin base, a lower jaw fully covered by the lower lip; 17-20 black vertical bars on the lower part of flank, a short suborbital spine with a shorter processus latero-caudalis that is less than one-fifth the length of the processus medio-caudalis, and seven branched dorsal-fin rays. The validity of the new species is corroborated by its monophyly, as evidenced by phylogenetic analysis based on the mitochondrial cytochrome b gene.